SOME ASPECTS OF VELOCITY CHARACTERISTICS AND THE DEEP STRUCTURE OF THE LITHOSPHERE IN PRECAMBRIAN SHIELDS - Trypilsky O.A.; Trypilska O.O. (My University, 2001)
This article presents the results of a study of the velocity characteristics and deep structure of the upper lithosphere in Precambrian shields, based on data from regional seismic investigations. An opinion on incompatibility between the results obtained and certain aspects of the new global tectonic theory is expressed.
Keywords: Precambrian; velocity characteristics; lithosphere; Докембрий; Precambrian